Compactness and completeness in partial metric spaces - Myronyk Vadym; Mykhaylyuk Volodymyr (Topology and its Applications, 2020)
We analyze compactness-like properties of sets in partial metric spaces and obtain the equivalence of several forms of the compactness for partial metric spaces. Moreover, we give a negative answer to a question from [8] on the existence of a bounded complete partial metric on a complete partial metric space.
Keywords: Compactness, Completeness,Countable compactness, Partial metric, Quasi-metric; Completeness; Countable compactness; Partial metric; Quasi-metric